The Effect of a Bimodal Grain Size Distribution on the Compressive Strength of Polycrystalline Ice. - Laughlin,James L (1985)
Previous studies have shown that grain size directly affects the strength of fresh-water equiaxed polycrystalline ice Ih, where strength decreases as grain size increases. This has been shown both in tension and compression at constant strain rates over a range of temperatures (-5 C, -1o C, -20C). The mechanical behavior of the ice is well described by the Hall-Petch relation. This thesis presents the results of a study to examine the effect of a bimodal grain size distribution on the compressive strength of equiaxed randomly oriented polycrystalline ice Ih. Laboratory prepared specimens of right circular ice consisting of different amounts of large (5.5 mm) and small(2.0 mm) grains by volume (75%/25L%, 50%/50%, 25%) were tested at -10 C in uniaxial unconfined compression. Tests were conducted at two strain rates, 0.00001/S and 0.001/s. Building on the results of Cannon (1985), this work establishes the law of mixtures for the compressive strength of a specimen composed of a bimodal mix of grains. First hypotheisized by Lee(1985), the law of mixtures states that the strength of a bimodal specimen is linearly dependent on the volume fraction of large and small grains. A single significant grain size may be used to charcterize the mechanical behavior of the specimen. Two possible candidates of a significant grain size are examined, one derived from the use of the Hall-Petch relation and the second being the average of the two grain sizes. Results show the use of the average is more expedient with little loss in accuracy. Master's thesis.